Accounting and analytical support of management of investment projects of the enterprise - Kovalchuk, Svitlana (Management and Entrepreneurship: Trends of Development, 2019)
Рurpose. The article is devoted to the clarification of the essence and components of the accounting and analytical support of investment’s management projects of the enterprise. Approach. The basic methods of research are general scientific methods of cognition: comparison, theoretical substantiation, methods of generalization and systematization, etc. Findings. Attention is paid to the definition of the concept of management of investment projects of the enterprise and its constituent elements. The structuring of the process of management of investment projects with allocation in it of three stages: pre-investment, stage of direct implementation of the project and the final stage is substantiated. The importance of accounting and analysis as elements providing information on management of investment projects is substantiated. The inexpediency of separation as part of the accounting and analytical support of control and audit is noted. The constituent elements forming the analytical provision of management of investment projects of the enterprise are determined. These include directions, methods, indicators, methods of analysis, criteria that the project must meet. Implications. The differentiation of the elements that form the accounting and analytical components of the accounting and analytical support of management of investment projects depending on the stages of implementation of such projects is substantiated. The basic elements of accounting and analytical support at all stages of management of an investment project are determined. Originality. The accounting and analytical support of management of investment projects plays an important informational role. Allocation of various accounting elements will increase the efficiency of its formation for modern enterprises. The selection of elements of analytical support at different stages of management of the investment project will increase awareness of the project.